RURAL LABOR AND RURAL ECONOMY - Catalin, Bologa (Economics of Agriculture, 2012)
The development of agriculture requires greater emphasis on human capital and, in addition to material capital, by providing better educational and health services in rural areas. The precarious situation prevailing in rural areas in education and health Romanian would justify granting of some priorities in this situation and prevent it worsening, especially in the future. In an economy like Romania, where agricultural production has significant annual fluctuations, without an ascending trend, to say that agriculture has the potential surplus of labor, food, and capacity of saving that requires only an appropriate agricultural policy for their mobilization ,is a static approach, incorrect transfer of resources to the problem. Unless agricultural production will increase or stabilize the investment and technical progress, it will become more significant part of available resources, production and transfer of income from non-agricultural sectors.